Dietary Habits and Nutritional Status of Youths Living in Rural and Semi-Urban Albania in the Ongoing Nutrition Transition: Preliminary Results - Ruden Cakoni; Stefania Moramarco; Argjend Kosiqi; Angela Andreoli; Ersilia Buonomo (Children)
Background: Albania is undergoing a demographic, epidemiological, and nutrition transition leading to an increased prevalence of overweight and obesity among new generations. Comprehensive studies on the nutritional status and dietary patterns of youths in the country are still lacking. Methods: A cross-sectional study was conducted on a convenience sample of students (10–18 years) attending secondary schools in rural and semi-urban areas (October–November 2024). Information collected included socio-demographic data, anthropometric measurements (weight, height), and adherence to the Mediterranean Diet (MD) (KIDMED). Factors influencing dietary patterns were investigated, with a multivariate logistic regression performed to identify key drivers for poor MD adherence (AOR 95% CI). Results: In total, 426 children (47.2% females) were interviewed. Over 20% of the sample was overweight or obese, with the prevalence of these diseases decreasing with age regardless of gender. The KIDMED score highlighted suboptimal MD adherence (4.6 ± 2.5 SD), with significant differences between females and males (4.1 ± 2.4 SD vs. 5.1 ± 2.4 SD, p < 0.001), especially in rural areas (3.9 ± 2.4 SD vs. 4.9 ± 2.5 SD, p = 0.003). Dietary quality tended to decline with age. Female gender was the strongest predictor of poor MD adherence (AOR 2.08 CI: 1.34–3.22; p = 0.001). Conclusions: The MD is a cornerstone for ensuring the Albanian population’s long-term health and well-being. This study holds significant public health relevance in a country with high mortality rates due to cardiovascular diseases. Future nutrition interventions focused on the poor MD adherence of new generations should take into consideration geographic, cultural, and social dimensions, including gender equality.